Pengaruh Tipe Perusahaan, Umur Perusahaan, Kinerja Keuangan, Corporate Governance, Struktur Modal Dan Growth Terhadap Pengungkapan Tanggung Jawab Lingkungan Pada Perusahaan Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia - Noveliana Noveliana; Thomas Sumarsan Goh; Elidawati Elidawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The company is currently trying to maintain its viability so that the company can develop and compete with other companies or the like. The very sluggish economic conditions had a direct impact on the company. One of the sectors affected is consumer goods companies. The purpose of this study was to determine the effect of company type, company age, financial performance, corporate governance, capital structure and growth on disclosure of environmental responsibility in consumer goods companies listed on the Indonesia Stock Exchange. The research population used was 51 consumer goods companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling technique is saturated because this research uses data on the type of company, age of the company, returns on assets, corporate governance, total debt, equity and sales. The results show that partially the type of company has no effect on the disclosure of environmental responsibility in consumer goods companies listed on the Indonesian stock exchange. Partially, the age of the company affects the disclosure of environmental responsibility in consumer goods companies listed on the Indonesian stock exchange. Partially, financial performance does not affect the disclosure of environmental responsibility in consumer goods companies listed on the Indonesian stock exchange. Partially, corporate governance affects the disclosure of environmental responsibility in consumer goods companies listed on the Indonesian stock exchange. Partially, the capital structure has no effect on the disclosure of environmental responsibility in consumer goods companies listed on the Indonesian stock exchange. Partially, growth does not affect the disclosure of environmental responsibility in consumer goods companies listed on the Indonesian stock exchange. Keywords : Company Type, Company Age, Financial Performance, Corporate Governance, Capital Structure, Growth, Environmental Responsibility.